Identification and Characterization of Key Chemical Constituents in Processed Gastrodia elata Using UHPLC-MS/MS and Chemometric Methods. (23rd October 2019) - Ye, Xide; Wang, Yanhong; Zhao, Jianping; Wang, Mei; Avula, Bharathi; Peng, Qiaozhen; Ouyang, Hui; Lingyun, Zhong; Zhang, Jinlian; Khan, Ikhlas A.
Abstract : Gastrodia elata Blume belongs to the Orchidaceae family. G. elata is often processed when used in traditional Chinese medicine (TCM). In the current study, a traditional processing method, known as "Jianchang Bang, " was applied. Steamed and dried (S&D) G. elata was processed with ginger juice for up to 5 days (GEP5D). An UHPLC-MS/MS combined with a chemometric method was developed for the analysis of processed G. elata along with the raw material as well as steamed and dried G. elata . As a result, the primary marker compounds were identified with the aid of TOF-MS and MS/MS analyses. Compared with the raw material of G. elata with GEP5D, three new parishin-type compounds were identified according to their retention time, accurate mass, and fragmentation patterns. The chromatographic peak areas for marker compounds, including S -(gastrodin)-glutathione, S -(4-hydroxybenzylamine)-glutathione, and parishin-type compounds, changed significantly. This result indicated that by applying the "Jianchang Bang" method, changes in chemical composition in G. elata contents were observed. The study also demonstrated that chemometric analysis is helpful in understanding the processing mechanism and will provide scientific support for the clinical application of G. elata .